2020
DOI: 10.36740/wlek202007111
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Insomnia Formation With Gastroesophageal Reflux Disease, Taking Into Account the Psychosomatic Status in Young People

Abstract: The aim: The work is aimed to study the formation mechanisms of sleep disturbances with GERD based on the determination of melatonin and serotonin indicators in the blood, psychosomatic status and quality of sleep, motor-secretory function of the esophagus and stomach in young people. Materials and methods: All 63 patients were with non-erosive GERD and insomnia. Among them, 32 with inhibitory personality type and 31 with excitable personality type. The control group is 25 people. Questionnaires were used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A connection was found between serotonin levels and the severity of pain and autonomic disorders. With a decrease in serotonin, the sensitivity of the body's pain system increases [16,17,18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…A connection was found between serotonin levels and the severity of pain and autonomic disorders. With a decrease in serotonin, the sensitivity of the body's pain system increases [16,17,18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical SP method (1) Paraffin sections were made dewax to water; (2) PBST liquid was used to clean each section for 10 min; (3) All sections were soaked in 3% H 2 O 2 for 15 min, which were protected from light to inactivate endogenous peroxidase; (4) PBST liquid was used to clean each section for 30 min; (5) Citrate was used to repair the antigen for 30 min, temperature of water kept between 92 and 99 ℃; (6) PBST liquid was used to clean each section for 30 min; (7) All sections were soaked in 0.1% Triton X-100 for 10 min to increase the permeability of the membrane; (8) PBST liquid was used to clean each section for 30 min; (9) After drying the slices, we dripped the 10% goat serum on the sections and then incubated them at room temperature for 60 min; (10) All the slices were dried again and were incubated with primary antibody (1/200 in diluent) overnight at 4 ℃; (11) Taken out of the fridge, each piece was first washed in PBST for discontinuation of reaction and then was cleaned in PBST liquid for 30 min; (12) After drying the slices, we dripped the second antibody on the sections and then incubated them at room temperature of 37 ℃ for 30 min; (13) PBST liquid was used to clean each section for 30 min; (14) After drying the slices, we dripped HRP on the sections and then incubated them at room temperature of 37 ℃ for 30 min; (15) PBST liquid was used to clean each section for 30 min; (16) DAB solution was used for coloration protected from light. When they showed brown, we washed the slices in pure water; (17) All the slices were rinsed by water for 10 min; (18) Hematoxylin was used for staining for 10 s; (19) All the slices were rinsed by water for 7-10 min; (20) All the slices were dehydrated, sealed by neutral balsam, and observed under light microscope.…”
Section: Immunohistochemistry Of Spinal Cord and Esophagus In Rats Pr...mentioning
confidence: 99%
“…With the deepening of research, more and more attention has been paid to the role of psychological factors in the occurrence of this disease. According to statistics, about 60% of patients with NERD have anxiety, depression, sleep disorders, autonomic nervous dysfunction, accompanied by decreased quality of life [10,11]. Previous studies have confirmed that psychological factors may cause visceral hypersensitivity through the brain gut axis [12,13], leading to mild acid reflux and other low-intensity stimulation that is not perceived by normal people, bringing acid reflux, heartburn, chest pain and other symptoms to patients, just like NERD.…”
Section: Introductionmentioning
confidence: 99%